Metode Pemahaman Hadis Ibnu Rajab Al-Hanbali Dalam Kitab Jâmi’ al-’Ulûm wa al-Hikam fî Syarh Khamsîn Hadîtsân min Jawâmi’ al-Kalim - Afrinaldi, Afrinaldi; Saputra, Edriagus; Fata, Azamel; Tranerts, San Dyeaurtty (Institut Agama Islam Sumatera Barat Pariaman, 2021)
Hadith is a relic and once the guidelines and instructions of life for the people of Islam, so that in practice it and gain understanding of the whole, the people of Islam requires a method of understanding the hadith that in accordance with the intent and purpose. One of the methods of understanding the hadiths against the traditions of the Prophet, namely the method of understanding the hadith of Ibn Rajab Al Hanbali in the book Jami 'al-' Ulum wa al-Hikam fi Syarh Khamsin Hadithan min Jawami’al- Kalim.The method of research this is a library research (Research Library) to collectthe data-data associated with sources of primary and secondary as well as perform the analysis of the data that has been there. The method of understanding the hadith that offered by Ibn Rajab al-Hanbali are contained in the book of the book Jami ‘al-Ulum wa al hikam fi Syarh Khamsin Haditsan min Jawami’ al-kalim, namely the method tahliliy ( analysis ) to give an explanation to the hadith of the, includes : Mentioning the route of transmission of hadith, lines other than transmission Hadith, Asbab al Wurud al-Hadis, Urgency Hadith, Ayat Al-Quran as ta’kidnya, mengurai Hadith global significance, explaining opinions Salaf Shaleh in the syarah Hadith, explaining other syarah and impinging on the fiqh of the hadith.